"At risk" languages and the road to recovery: a case from the Yukon. Issue 3 (16th March 2022) - Meek, Barbra A.
ABSTRACT: This article traces the various ways that 'languages at risk' in the Yukon Territory, Canada, are imagined and managed across a range of 'stakeholders.' Predicated on a history of oppression and the management of risk in the U.S. and Canada, aboriginal language endangerment has arisen from insecurities about communicative diversity. Conversely language revitalization has arisen from insecurities about the loss of diversity. As this article demonstrates, ideologies of loss and the insecurities entailed therein resonate differently across different speakers, language activists, and institutions, resulting in different perceptions of loss, different experiences of risk, and different approaches to recovery. Moving from policy and the institutionalization of aboriginal languages to people's reflections and concerns about their own welfare, this article argues that insecurities about language are ultimately insecurities about other vulnerabilities, including the shifting political-moral terrain of the nation-state and First Nations.